Three new mealybug species (Hemiptera: Coccomorpha: Pseudococcidae) from Iran - Moghaddam, Masumeh (Zootaxa, 2018)
Three new mealybug species, Dysmicoccus caspianensis sp. n., Dysmicoccus zagrosicus sp. n. and Phenacoccus bromi sp. n. (Hemiptera: Pseudococcidae), collected from protected areas in Iran, are described and illustrated. The identification keys to Phenacoccus species lacking ventral multilocular disc pores and Dysmicoccus species in Iran are presented.